Bogseranordning för ny, miljövänlig räddningsbåt - Håland, Elias; Persson, Kristoffer (My University, 2023)
The aim of this thesis project was to develop a fully functioning towing device prototype for the Swedish Sea Rescue Society's new electric rescue boat. The work was conducted at the Department of Industrial and Materials Science at Chalmers University of Technology. What sets the towing device apart from previous versions used by the Sea Rescue Society is the placement. The development of the towing device has focused on making it ergonomic, user-friendly, and safe. To ensure this, a reliable automatic emergency release is required, which forms the core of the project. Through systematic product development work, relevant data and knowledge have been collected and evaluated. A requirements specification has been compiled, followed by the generation of sub-solutions. A morphological matrix transformed sub-solutions into solution groups. The solution groups were assessed, and the inferior ones were eliminated using an elimination and Pugh matrix. Evaluation of the remaining concepts was conducted to identify issues and weaknesses. Subsequently, more alternatives were eliminated, leaving only one final concept. The final concept has been described in more detail. During the course of the project, the work has shifted towards investigating and preparing for the Sea Rescue Society's continued development of a towing device. Suggestions for further development are provided at the end of the report.